Calcium sensing receptor in developing human airway smooth muscle. Issue 8 (9th January 2019) - Roesler, Anne M.; Wicher, Sarah A.; Ravix, Jovanka; Britt, Rodney D.; Manlove, Logan; Teske, Jacob J.; Cummings, Katelyn; Thompson, Michael A.; Farver, Carol; MacFarlane, Peter; Pabelick, Christina M.; Prakash, Y.S.
Abstract: Airway smooth muscle (ASM) regulation of airway structure and contractility is critical in fetal/neonatal physiology in health and disease. Fetal lungs experience higher Ca 2+ environment that may impact extracellular Ca 2+ ([Ca 2+ ]o ) sensing receptor (CaSR). Well‐known in the parathyroid gland, CaSR is also expressed in late embryonic lung mesenchyme. Using cells from 18‐22 week human fetal lungs, we tested the hypothesis that CaSR regulates intracellular Ca 2+ ([Ca 2+ ]i ) in fetal ASM (fASM). Compared with adult ASM, CaSR expression was higher in fASM, while fluorescence Ca 2+ imaging showed that [Ca 2+ ]i was more sensitive to altered [Ca 2+ ]o . The fASM [Ca 2+ ]i responses to histamine were also more sensitive to [Ca 2+ ]o (0–2 mM) compared with an adult, enhanced by calcimimetic R568 but blunted by calcilytic NPS2143. [Ca 2+ ]i was enhanced by endogenous CaSR agonist spermine (again higher sensitivity compared with adult). Inhibition of phospholipase C (U73122; siRNA) or inositol 1, 4, 5‐triphosphate receptor (Xestospongin C) blunted [Ca 2+ ]o sensitivity and R568 effects. NPS2143 potentiated U73122 effects. Store‐operated Ca 2+ entry was potentiated by R568. Traction force microscopy showed responsiveness of fASM cellular contractility to [Ca 2+ ]o and NPS2143. Separately, fASM proliferation showed sensitivity to [Ca 2+ ]o and NPS2143. These results demonstrate functional CaSR in developing ASM that modulates airway contractility and proliferation. Abstract : We demonstrate expression of functional extracellular calcium‐sensing receptor (CaSR) in human fetal airway smooth muscle. Although better known in the parathyroid, kidney, and bone, CaSR in the lung has the potential to influence airway contractility and remodeling (proliferation) in the context of early postnatal development. The relevance of lung CaSR further lies in its potential modulation by insults, such as oxygen or inflammation that leads to neonatal and pediatric asthma particularly in the context of prematurity.